2005
DOI: 10.1152/ajpgi.00037.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of intestinal alkaline phosphatase gene expression by Cdx1 and Cdx2

Abstract: -We have examined the role that the caudal-related homeobox transcription factors Cdx1 and Cdx2 play in activating the enterocyte differentiation marker gene intestinal alkaline phosphatase (IAP). Human colon cancer Caco-2 cells were transiently transfected with Cdx1 and/or Cdx2, and semiquantitative RT-PCR was used to study the effects on IAP mRNA expression. Transfections with a variety of IAP-luciferase reporter constructs were used to identify a Cdx response element located within the human IAP gene promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
(57 reference statements)
0
29
0
Order By: Relevance
“…Under in vivo conditions in which endodermal GATA family members are coexpressed in enteric epithelial cells and interact physically and functionally (12,22,23), such preferential occupation of GATA sites by intestinal GATA factors could result in differential regulation of GATA target genes. In support of the second possibility, a multitude of factors such as Sp1, Sp3, KLF4, HNF4, thyroid hormone receptor, Cdx1 and Cdx2, and Kruppel type zinc finger protein, ZBP-89, have been reported to bind to IAP promoter and regulate IAP promoter activity (3,37,41,52,53,65). Several of these factors bind in close proximity to the nine potential GATA sites present in the IAP promoter.…”
Section: Discussionmentioning
confidence: 95%
“…Under in vivo conditions in which endodermal GATA family members are coexpressed in enteric epithelial cells and interact physically and functionally (12,22,23), such preferential occupation of GATA sites by intestinal GATA factors could result in differential regulation of GATA target genes. In support of the second possibility, a multitude of factors such as Sp1, Sp3, KLF4, HNF4, thyroid hormone receptor, Cdx1 and Cdx2, and Kruppel type zinc finger protein, ZBP-89, have been reported to bind to IAP promoter and regulate IAP promoter activity (3,37,41,52,53,65). Several of these factors bind in close proximity to the nine potential GATA sites present in the IAP promoter.…”
Section: Discussionmentioning
confidence: 95%
“…Cdx2 is a transcriptional activator of a number of intestine-specific genes, including MUC2, sucrose-isomaltase, guanylyl cyclase C, and intestinal alkaline phosphatase (IAP). [37][38][39][40][41] Furthermore, ATOH1 also contributes to induction of the inter-regulation network with Cdx2 and indirectly stimulates cellular transdifferentiation into IM.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was recently shown that CDX2 alters the proliferation of intestinal crypt cells and stimulates the expression of distinct intestinal differentiation markers 14,15 . We therefore examined CDX2 mRNA by Real-Time PCR in T84 cells co-cultured with normal, CD or UC LPL for 4 days (Fig 3).…”
Section: Lpl Induce An Increase In the Expression Of Cdx-2 In Colomentioning
confidence: 99%
“…In contrast to CDX1 which is mainly expressed in the crypt compartment (although not restricted to proliferative cells) 14 , the CDX2 homeoproteins are mainly expressed in differentiating enterocytes 15 , triggering growth retardation and cell differentiation by overexpression in several intestinal lines in vitro 16 . Furthermore, genes regulated by either CDX1 or CDX2 generally define a functional differentiated phenotype, such as sucraseisomaltase 16 , dipeptidyl peptidase IV 14 , or intestinal alkaline phosphatase (IAP) 15 .…”
Section: Introductionmentioning
confidence: 99%